23k-k+38=12

Combine 23 and k.

2k3-k+38=12

To write -k as a fraction with a common denominator, multiply by 33.

2k3-k⋅33+38=12

Simplify terms.

Combine -k and 33.

2k3+-k⋅33+38=12

Combine the numerators over the common denominator.

2k-k⋅33+38=12

2k-k⋅33+38=12

Simplify each term.

Simplify the numerator.

Factor k out of 2k-k⋅3.

Factor k out of 2k.

k⋅2-k⋅33+38=12

Factor k out of -k⋅3.

k⋅2+k(-1⋅3)3+38=12

Factor k out of k⋅2+k(-1⋅3).

k(2-1⋅3)3+38=12

k(2-1⋅3)3+38=12

Multiply -1 by 3.

k(2-3)3+38=12

Subtract 3 from 2.

k⋅-13+38=12

k⋅-13+38=12

Move -1 to the left of k.

-1⋅k3+38=12

Move the negative in front of the fraction.

-k3+38=12

-k3+38=12

-k3+38=12

Subtract 38 from both sides of the equation.

-k3=12-38

To write 12 as a fraction with a common denominator, multiply by 44.

-k3=12⋅44-38

Write each expression with a common denominator of 8, by multiplying each by an appropriate factor of 1.

Multiply 12 and 44.

-k3=42⋅4-38

Multiply 2 by 4.

-k3=48-38

-k3=48-38

Combine the numerators over the common denominator.

-k3=4-38

Subtract 3 from 4.

-k3=18

-k3=18

Multiply both sides of the equation by -3.

-3⋅(-k3)=-3⋅18

Simplify -3⋅(-k3).

Cancel the common factor of 3.

Move the leading negative in -k3 into the numerator.

-3⋅-k3=-3⋅18

Factor 3 out of -3.

3(-1)⋅-k3=-3⋅18

Cancel the common factor.

3⋅-1⋅-k3=-3⋅18

Rewrite the expression.

-1⋅(-k)=-3⋅18

-1⋅(-k)=-3⋅18

Multiply.

Multiply -1 by -1.

1⋅k=-3⋅18

Multiply k by 1.

k=-3⋅18

k=-3⋅18

k=-3⋅18

Simplify -3⋅18.

Combine -3 and 18.

k=-38

Move the negative in front of the fraction.

k=-38

k=-38

k=-38

The result can be shown in multiple forms.

Exact Form:

k=-38

Decimal Form:

k=-0.375

Solve for k 2/3k-k+3/8=1/2